Effects of Voluntary Product Recall on Consumer’s Trust - Luiza Venzke Bortoli; Valeria Freundt (BBR: Brazilian Business Review)
This study analyzed the impact of voluntary product recall due to product failure on consumer’s trust. Since trust is composed by integrity, competence and benevolence, this study verified the mediator effect of these constructs on the relation between recall and trust. Once trust is essential for the establishment of a relationship between companies and consumers, this research also evaluated the effects of relational and transactional purchase situations on consumer’s trust and its constructs. We conducted an experimental study with a 2 (recall: control; voluntary recall) x 2 (purchase situation: relational; transactional) between subjects design. The results indicated that voluntary recall has a positive effect on the variables analyzed. Integrity and competence fully mediate the relation between voluntary recall and trust. Purchase situation moderates the effect of voluntary recall on competence.